2021
DOI: 10.3390/ijms22168686
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Antigens Reduced the Inhibition Effect of Capsaicin on Cal 27 Oral Cancer Cell Proliferation

Abstract: Oral cancer is a major global health problem with high incidence and low survival rates. The oral cavity contains biofilms as dental plaques that harbour both Gram-negative and Gram-positive bacterial antigens, lipopolysaccharide (LPS) and lipoteichoic acid (LTA), respectively. LPS and LTA are known to stimulate cancer cell growth, and the bioactive phytochemical capsaicin has been reported to reverse this effect. Here, we tested the efficacy of oral cancer chemotherapy treatment with capsaicin in the presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(27 citation statements)
references
References 20 publications
6
21
0
Order By: Relevance
“…We recently reported that the combination of bacterial antigens, lipoteichoic acid (LTA) and lipopolysaccharide (LPS), resulted in increased proliferation of the oral cancer cell Cal 27, but not SCC4, SCC9 and SCC25, compared to stimulation with LPS alone [2]. We then developed an in vitro assay to measure the efficacy of drug treatment on Cal 27 in the presence of bacterial antigens, and examined the effect of capsaicin, which is known to induce apoptosis in several cancers [3]. The bacterial antigens LPS and LTA decreased the anti-cancer efficacy of capsaicin, both for antigenic stimulation given prior to and concurrently with this drug [3].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…We recently reported that the combination of bacterial antigens, lipoteichoic acid (LTA) and lipopolysaccharide (LPS), resulted in increased proliferation of the oral cancer cell Cal 27, but not SCC4, SCC9 and SCC25, compared to stimulation with LPS alone [2]. We then developed an in vitro assay to measure the efficacy of drug treatment on Cal 27 in the presence of bacterial antigens, and examined the effect of capsaicin, which is known to induce apoptosis in several cancers [3]. The bacterial antigens LPS and LTA decreased the anti-cancer efficacy of capsaicin, both for antigenic stimulation given prior to and concurrently with this drug [3].…”
Section: Introductionmentioning
confidence: 99%
“…We then developed an in vitro assay to measure the efficacy of drug treatment on Cal 27 in the presence of bacterial antigens, and examined the effect of capsaicin, which is known to induce apoptosis in several cancers [3]. The bacterial antigens LPS and LTA decreased the anti-cancer efficacy of capsaicin, both for antigenic stimulation given prior to and concurrently with this drug [3].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations